Question and Answers Forum

All Questions      Topic List

Others Questions

Previous in All Question      Next in All Question      

Previous in Others      Next in Others      

Question Number 82929 by VBash last updated on 26/Feb/20

if 2B+A=45°  show that;  tan B= ((1−2tanA−tan^2 A)/(1+2tanA−tan^2 A))

if2B+A=45°showthat;tanB=12tanAtan2A1+2tanAtan2A

Answered by jagoll last updated on 26/Feb/20

A+B = 45^o  − B  tan (A+B) = tan (45^o −B)  ((tan A+tan B)/(1−tan A.tan B)) = ((1−tan B)/(1+tan B))  (tan A+tan B)(1+tan B) =   (1−tanA tan B)(1−tan B)  tan A = ((tan^2 B+2tan B−1)/(tan^2 B−2tan B−1))  or tan A = ((1−2tan B−tan^2 B)/(1+2tan B−tan^2 B))

A+B=45oBtan(A+B)=tan(45oB)tanA+tanB1tanA.tanB=1tanB1+tanB(tanA+tanB)(1+tanB)=(1tanAtanB)(1tanB)tanA=tan2B+2tanB1tan2B2tanB1ortanA=12tanBtan2B1+2tanBtan2B

Commented by john santu last updated on 26/Feb/20

good sir

goodsir

Commented by som(math1967) last updated on 26/Feb/20

How tan(45°−B)=((1−tanA)/(1+tanA)) ???

Howtan(45°B)=1tanA1+tanA???

Commented by jagoll last updated on 26/Feb/20

hahaha..sorry. it my typo

hahaha..sorry.itmytypo

Answered by TANMAY PANACEA last updated on 26/Feb/20

tan(2B)=tan(45−A)  let tanA=a   tanB=b  ((2b)/(1−b^2 ))=((1−a)/(1+a))  ((2b+1−b^2 )/(2b−1+b^2 ))=((1−a+1+a)/(1−a−1−a))  ((2b+1−b^2 )/(2b−1+b^2 ))=(2/(−2a))  ((−a)/1)=((2b−1+b^2 )/(2b+1−b^2 ))  a=((b^2 +2b−1)/(b^2 −2b−1))  pls recheck the question

tan(2B)=tan(45A)lettanA=atanB=b2b1b2=1a1+a2b+1b22b1+b2=1a+1+a1a1a2b+1b22b1+b2=22aa1=2b1+b22b+1b2a=b2+2b1b22b1plsrecheckthequestion

Commented by jagoll last updated on 26/Feb/20

it that the question wrong

itthatthequestionwrong

Terms of Service

Privacy Policy

Contact: info@tinkutara.com